The Buck, the Bull, and the Dream of the Stag: Some unexpected weeds of the Anthropocene - Anna Tsing (Suomen Antropologi, 2017)
Landscapes are sites of struggle for many ways of being, human and nonhuman. This paper draws attention to weedy landscapes as places for anthropologists to get to know the Anthropocene, in all its heterogeneity. Weeds are creatures of human disturbance, and the forms they take depend on the kind of disturbance and the kind of unmanagement that follows. Weeds guide us to coordinations between human and nonhuman projects of world making—as exemplified, in this paper, by ‘the dream of the stag,’ an axis linking the imaginations of red deer and hunters, who are both opportunistic interlopers in the research site. The research concerns the weedy ‘auto-rewilding’ of a former brown coal mine in the sandy glacial outwash of central Jutland, Denmark. Previously an anthropogenic moorland used mainly for grazing sheep, labor-intensive mining emerged during World War II but was abandoned in 1970, leaving sand piles and holes that became acidic lakes. Beginning in 2013, Aarhus University Research on the Anthropocene (AURA) began an experiment in fieldwork there that crosses natural science/social science boundaries, and this paper emerges from that continuing encounter. The dream of the stag draws the analysis into the political ecology of weedy emergence, which in turn opens reflections on more-than-human world-making and the possibility of thinking Anthropocene timelines through weeds.